2020
DOI: 10.1177/2292550320954093
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Postoperative Dependency Protocols Following Lower Limb Microvascular Reconstruction: A National Survey and Literature Review

Abstract: Introduction: Microsurgical free tissue transfer for lower limb reconstruction presents unique challenges in the postoperative period where dependency promotes interstitial fluid diffusion and reduced tissue perfusion. Management of flap edema, venous congestion, and ischaemic conditioning is critical for flap survival. Little evidence exists to guide postoperative protocols in the initiation and progression of lower extremity dangle, monitoring, and anticoagulation. We aim to describe current trends for posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Free flaps applied to the lower limbs may be especially prone to venous congestion due to their dependent position, leading to increased oedema, reduced perfusion pressure, compression of the vascular pedicle, and, ultimately, loss of the flap [16][17][18] . It has also been reported that lower limb free flaps may be at increased risk of venous congestion compared to free flaps applied elsewhere in the body, even when the limb is kept elevated [19] . In light of concerns around venous congestion, the best time from which to permit weight bearing is uncertain, and many centres have introduced "dangling protocols", the aim of which is to introduce gravitational dependency gradually to allow adaptive physiological responses to take place and reduce the risk of flap loss [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Free flaps applied to the lower limbs may be especially prone to venous congestion due to their dependent position, leading to increased oedema, reduced perfusion pressure, compression of the vascular pedicle, and, ultimately, loss of the flap [16][17][18] . It has also been reported that lower limb free flaps may be at increased risk of venous congestion compared to free flaps applied elsewhere in the body, even when the limb is kept elevated [19] . In light of concerns around venous congestion, the best time from which to permit weight bearing is uncertain, and many centres have introduced "dangling protocols", the aim of which is to introduce gravitational dependency gradually to allow adaptive physiological responses to take place and reduce the risk of flap loss [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Seven of these studies reported comparable outcomes with regard to flap survival, complication rates and adverse effects, regardless of the used vasoactive agent. No benefit was found for any particular antithrombotic drug and no consensus was found for a certain anticoagulation regime [1,[13][14][15][16][17][18].…”
Section: Article Screeningmentioning
confidence: 99%
“…Likewise, seven systematic reviews reported similar outcomes with regard to flap survival, complication rates and adverse effects. No advantage was found for any particular anticoagulation regime or specific drug [1,[13][14][15][16][17][18]. Two studies found higher odds for complications either with the combination of heparin and aspirin or intravenous heparin in terms of postoperative hematoma.…”
Section: Clinical Studiesmentioning
confidence: 99%